Minor impact of probiotic bacteria and egg white on Tenebrio molitor growth, microbial composition, and pathogen infection - Savio, Carlotta; Herren, Pascal; Rejasse, Agnès; Rios, Alfredo; Bourelle, William; Bruun-Jensen, Annette; Lecocq, Antoine; van Loon, Joop J. A.; Nielsen-LeRoux, Christina (Frontiers in Insect Science, 2024)
The industrial rearing for feed and food purposes of the yellow mealworm, Tenebrio molitor, on agricultural by-products may expose larvae and adults to entomopathogens used as biocontrol agents in crop production. Bacterial spores/toxins or fungal conidia from species such as Bacillus thuringiensis (Bt) or Metarhizium brunneum, respectively, could affect the survival and growth of the insects. Therefore, the aim of this study was to investigate the potential benefits of a wheat bran diet supplemented with probiotic bacteria and dried egg white, on larval development, survival and effects on gut microbiome composition. Two probiotic bacterial species, Pediococcus pentosaceus KVL B19-01 and Lactiplantibacillus plantarum WJB were added to wheat bran feed with and without dried egg white, as an additional protein source, directly from neonate larval hatching until reaching a body mass of 20 mg. Then larvae from the various diets were exposed during 72 h to B. thuringiensis, M. brunneum or their combination. Larval survival and growth were recorded for 14 days and the bacterial microbiota composition was analysed by 16S rDNA sequencing prior to pathogen exposure and at day 3 and 11 after inoculation with the pathogens. The results showed increased survival for T. molitor larvae reared on feed supplemented with P. pentosaceus in case of co-infection. Larval growth was also impacted in the co-infection treatment. No significant impact of egg white or of P. pentosaceus on larval growth was recorded, while Lb. plantarum addition resulted in a minor increase in individual mass gain compared with infected larvae without the latter probiotic. At day 14, Bt was no longer detected and overall the bacterial community composition of the larvae was similar in all treatments. Meanwhile, the relative OTU abundance depended on day, diet and probiotic. Interestingly, P. pentosaceus was present throughout the experiments, while Lb. plantarum was not found at a detectable level, although its transient presence slightly improved larval performance. Overall, this study confirms the potential benefits of some probiotics during the development of T. molitor while underlining the complexity of the relationship between the host and its microbiome.